Tracing early life stress in human molar morphology: Associations between linear enamel hypoplasia and maxillary first molar form - Erin C. Blankenship-Sefczek; Alan H. Goodman; Mark Hubbe; John P. Hunter; Timothy M. Sefczek; Debbie Guatelli-Steinberg (PLoS ONE, 2026)
Permanent tooth structures can respond to environmental disruptions even after the initiation of hard tissue deposition at the cusp tips, affecting dental morphology. In bioarcheological studies, linear enamel hypoplasia (LEH) provides evidence of both the presence and timing of developmental stressors that can occur during first molar odontogenesis. Yet, previous studies used LEH from the entirety of the anterior tooth surface to relate disruptions to changes in permanent tooth morphology, which could conflate causality by misrepresenting the timing of events. This study assessed associations between LEH formed during maxillary permanent first molar development and dental characteristics of these molars in contemporary humans with known health and nutritional histories from Tezonteopan, Mexico. LEH were observed in the field, and dental characteristics (crown size, principal cusp spacing, expression of cusp 5 and Carabelli trait) were observed on maxillary dental casts taken of the same adolescent study participants (n = 54). Statistical analyses included multivariate- and generalized linear models, and Principal Component Analyses. Slightly larger crown sizes, decreased buccolingual principal cusp spacing, and a slight decrease in cusp 5 expression were associated with the presence of LEH. The decrease in cusp spacing and decrease in cusp 5 expression follow expectations of the Patterning Cascade Model. Our results differ in some ways from those of previous studies possibly due to our focus on LEH defects forming during molar developmental periods. Our findings support the growing body of studies highlighting the unpredictability of molar morphology in the presence of developmental disruptions.